On some properties of a generalized class of close-to-starlike functions / Ajab Bai Akbarally and Nor Siti Khadijah Arunah - Akbarally, Ajab Bai; Arunah, Nor Siti Khadijah (Universiti Teknologi MARA Press (Penerbit UiTM), 2019)
In this paper, we consider a new class of close-to-starlike functions denoted by ...